Christian contradictions: the structures of Lutheran and Catholic thought - Hampson, Margaret Daphne (Cambridge University Press, 2001)
Catholic thought and Lutheran thought are differently structured, embodying divergent conceptions of self and God. Failing to grasp the Lutheran paradigm, Catholics have wrenched Luther into an inappropriate framework. Roman/Lutheran ecumenism, culminating in the 'Joint Declaration' of 1999, attempts to reconcile incompatible systems, based on different philosophical presuppositions. Drawing on a wealth of material, both Continental and Anglo-Saxon, the author thinks through these structural questions within a historical context. But how - within a religion of revelation - can God be conceptualised as both foundational to the self and yet also as an 'other' with whom the self inter-relates? Kierkegaard is shown in a complex model to hold together strengths which historically have been exemplified by the two traditions. This is an important work in systematic theology which considers questions quite fundamental to Western religion. It should be of interest to theologians of all backgrounds and also to church historians.